Parental perspectives on learning disability: Omani context - Al-Bahrani, Muna (Advances in Social Sciences Research Journal, 2021)
this study examined parents’ attitudes concerning the nature of learning difficulties (N =93) using questionnaire consists of three domains including awareness of the nature of learning difficulties, collaboration with school, and satisfaction towards the program. Results showed parents’ attitude towards learning difficulties program was positive in three domains. Suggestions are presented for further research.